Pengaruh Kinerja Pasar dan Makro Ekonomi Terhadap Return Saham(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2008-2011) - Gusganda Suria Manda (Accounthink, 2016)
Target of this research to analyze Price Book Value to influence (PBV), Earning per Share (EPS), Price Earning Ratio (PER), rate, rate of interest and inflation to share return. Pursuant to the mentioned hence this research take title ”Pengaruh Kinerja Pasar Dan Makro Ekonomi Terhadap Return Saham (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2008-2011)”. Population in this research is manufacturing business which enlist in Effect Exchange Indonesia during year 2008 until year 2011 amounting to 153 company. In election of sample done with sampling purposive method with manufacturing business criterion which enlist in BEI before year 2005 and compile annual financial statement by successively year 2008 - 2011 is so that obtained by counted 88 company. Pursuant to result of research which have been done by hence can know by Price Book Value to (PBV) have an effect on positive and significant to share return. Earning per Share (EPS) have an effect on positive and do not significant to share return. Price Earning Ratio (PER) have an effect on positive and do not significant to share return. Rupiah rate to dollar have an effect on significant and negativity to share return. Rate of interest have an effect on do not significant and negativity to share return and Inflation have an effect on positive and do not significant to share return.